Definitions

Chain rule

Chain rule

In calculus, the chain rule is a formula for the derivative of the composite of two functions.

In intuitive terms, if a variable, y, depends on a second variable, u, which in turn depends on a third variable, x, then the rate of change of y with respect to x can be computed as the rate of change of y with respect to u multiplied by the rate of change of u with respect to x.

Informal discussion

For an explanation of notation used in this section, see Function composition.
The chain rule states that, under appropriate conditions,

(f circ g)'(x) = f'(g(x)) g'(x),,

which in short form is written as

(f circ g)' = f'circ gcdot g'.

Alternatively, in the Leibniz notation, the chain rule is

frac {dy}{dx} = frac {dy} {du} cdotfrac {du}{dx}.

In integration, the counterpart to the chain rule is the substitution rule.

Theorem

The chain rule in one variable may be stated more completely as follows. Let g be a real-valued function on (a,b) which is differentiable at c ∈ (a,b); and f a real-valued function defined on an interval I containing the range of g and g(c) as an interior point. If f is differentiable at g(c), then

  • (fcirc g)(x) is differentiable at x = c, and
  • (fcirc g)'(c) = f'(g(c))g'(c).

Examples

Example I

Suppose that a mountain climber ascends at a rate of 0.5 kilometers per hour. The temperature is lower at higher elevations; suppose the rate by which it decreases is 6 °C per kilometer. If one multiplies 6 °C per kilometer by 0.5 kilometer per hour, one obtains 3 °C per hour. This calculation is a typical chain rule application.

Example II

Consider the function f(x) = (x2 + 1)3. Since f(x) = h(g(x)) where g(x) = x2 + 1 and h(x) = x3 it follows from the chain rule that

f '(x) , = h '(g(x)) g ' (x) , = 3(g(x))^2(2x) , = 3(x^2 + 1)^2(2x) ,
= 6x(x^2 + 1)^2. ,

In order to differentiate the trigonometric function

f(x) = sin(x^2),,
one can write f(x) = h(g(x)) with h(x) = sin x and g(x) = x2. The chain rule then yields
f'(x) = 2x cos(x^2) ,
since h′(g(x)) = cos(x2) and g′(x) = 2x.

Example III

Differentiate arctan(sin x).

frac{d}{dx}arctan x = frac{1}{1+x^2}

Thus, by the chain rule,

frac{d}{dx}arctan f(x) = frac{f'(x)}{1+f^2(x)},,

and in particular,

frac{d}{dx}arctan(sin x) = frac{cos x}{1+sin^2 x},.

Chain rule for several variables

The chain rule works for functions of more than one variable. Consider the function z = f(x, y) where x = g(t) and y = h(t), and g(t) and h(t) are differentiable with respect to t, then
{ dz over dt}={partial z over partial x}{dx over dt}+{partial z over partial y}{dy over dt}.

Suppose that each argument of z = f(u, v) is a two-variable function such that u = h(x, y) and v = g(x, y), and that these functions are all differentiable. Then the chain rule would look like:

{partial z over partial x}={partial z over partial u}{partial u over partial x}+{partial z over partial v}{partial v over partial x}

{partial z over partial y}={partial z over partial u}{partial u over partial y}+{partial z over partial v}{partial v over partial y}.

If we considered

vec r = (u,v)
above as a vector function, we can use vector notation to write the above equivalently as the dot product of the gradient of f and a derivative of vec r:
frac{partial f}{partial x}=vec nabla f cdot frac{partial vec r}{partial x}.

More generally, for functions of vectors to vectors, the chain rule says that the Jacobian matrix of a composite function is the product of the Jacobian matrices of the two functions:

frac{partial(z_1,ldots,z_m)}{partial(x_1,ldots,x_p)} = frac{partial(z_1,ldots,z_m)}{partial(y_1,ldots,y_n)} frac{partial(y_1,ldots,y_n)}{partial(x_1,ldots,x_p)}.

Proof of the chain rule

Let f and g be functions and let x be a number such that f is differentiable at g(x) and g is differentiable at x. Then by the definition of differentiability,

g(x+delta)-g(x)= delta g'(x) + epsilon(delta)delta ,
where ε(δ) → 0 as δ → 0. Similarly,
f(g(x)+alpha) - f(g(x)) = alpha f'(g(x)) + eta(alpha)alpha ,
where η(α) → 0 as α → 0.

Now

f(g(x+delta))-f(g(x)), = f(g(x) + delta g'(x)+epsilon(delta)delta) - f(g(x)) ,
= alpha_delta f'(g(x)) + eta(alpha_delta)alpha_delta ,

where

alpha_delta = delta g'(x) + epsilon(delta)delta. ,
Observe that as δ → 0, αδ/δg′(x) and αδ → 0, and thus η(αδ) → 0. It follows that
frac{f(g(x+delta))-f(g(x))}{delta} to g'(x)f'(g(x))mbox{ as } delta to 0.

The fundamental chain rule

The chain rule is a fundamental property of all definitions of derivative and is therefore valid in much more general contexts. For instance, if E, F and G are Banach spaces (which includes Euclidean space) and f : EF and g : FG are functions, and if x is an element of E such that f is differentiable at x and g is differentiable at f(x), then the derivative (the Fréchet derivative) of the composition g o f at the point x is given by

mbox{D}_xleft(g circ fright) = mbox{D}_{fleft(xright)}left(gright) circ mbox{D}_xleft(fright).

Note that the derivatives here are linear maps and not numbers. If the linear maps are represented as matrices (namely Jacobians), the composition on the right hand side turns into a matrix multiplication.

A particularly clear formulation of the chain rule can be achieved in the most general setting: let M, N and P be Ck manifolds (or even Banach-manifolds) and let

f : MN and g : NP

be differentiable maps. The derivative of f, denoted by df, is then a map from the tangent bundle of M to the tangent bundle of N, and we may write

mbox{d}left(g circ fright) = mbox{d}g circ mbox{d}f.

In this way, the formation of derivatives and tangent bundles is seen as a functor on the category of C manifolds with C maps as morphisms.

Tensors and the chain rule

See tensor field for an advanced explanation of the fundamental role the chain rule plays in the geometric nature of tensors.

Higher derivatives

Faà di Bruno's formula generalizes the chain rule to higher derivatives. The first few derivatives are
frac{d (f circ g) }{dx} = frac{df}{dg}frac{dg}{dx}
frac{d^2 (f circ g) }{d x^2} = frac{d^2 f}{d g^2}left(frac{dg}{dx}right)^2 + frac{df}{dg}frac{d^2 g}{dx^2}
frac{d^3 (f circ g) }{d x^3} = frac{d^3 f}{d g^3} left(frac{dg}{dx}right)^3 + 3 frac{d^2 f}{d g^2} frac{dg}{dx} frac{d^2 g}{d x^2} + frac{df}{dg} frac{d^3 g}{d x^3}
frac{d^4 (f circ g) }{d x^4} =frac{d^4 f}{dg^4} left(frac{dg}{dx}right)^4 + 6 frac{d^3 f}{d g^3} left(frac{dg}{dx}right)^2 frac{d^2 g}{d x^2} + frac{d^2 f}{d g^2} left{ 4 frac{dg}{dx} frac{d^3 g}{dx^3} + 3left(frac{d^2 g}{dx^2}right)^2right}

+ frac{df}{dg}frac{d^4 g}{dx^4}.

See also

References

External links

Search another word or see Chain Ruleon Dictionary | Thesaurus |Spanish
Copyright © 2014 Dictionary.com, LLC. All rights reserved.
  • Please Login or Sign Up to use the Recent Searches feature
FAVORITES
RECENT

;